Pharmacokinetic and pharmacodynamic comparison of subcutaneous versus intramuscular leuprolide acetate formulations in male subjects. Issue 2 (February 2018) - Saltzstein, Daniel; Shore, Neal D.; Moul, Judd W.; Chu, Franklin; Concepcion, Raoul; de la Motte, Stephan; McLane, John A.; Atkinson, Stuart; Yang, Alex; Crawford, E. David
Background: The aim of this study was to compare the pharmacokinetics (PK) and pharmacodynamics (PD) of two distinct formulations of leuprolide acetate (LA); subcutaneous (SC) injection and intramuscular (IM) injection. Methods: A total of 32 healthy men were randomized to receive a single 7.5 mg injection of SC-LA ( n = 16) or IM-LA ( n = 16) in this phase I, open-label, parallel-group study. PK was assessed via LA concentrations, and PD via serum luteinizing hormone (LH) and testosterone (T) concentrations. Results: The initial surge of LA was higher for IM-LA than SC-LA (Cmax 27 ± 4.9 versus 19 ± 8.0 ng/ml, respectively), with a shorter tmax (1.0 ± 0.4 versus 2.1 ± 0.8 h). The duration of quantifiable LA concentration was longer for SC-LA (up to 56 versus 42 days for SC-LA and IM-LA, respectively). Median LH concentrations in both groups rapidly increased, followed by gradual decrease. However, SC-LA demonstrated a longer duration of LH suppression, with median levels remaining below 1.0 IU/l through Day 56 compared with IM-LA where LH started to rise by Day 35. Consequently, serum T began to increase by Day 42 in the IM-LA group, with only four subjects maintaining levels ⩽50 ng/dl, compared with 14 subjects in the SC-LA group. By Day 56, 13 SC-LA subjects maintained serum T levels ⩽50 ng/dl. Both SC-LA and IM-LA were well tolerated. Conclusions: Both formulations demonstrated consistent delivery of drug over 1 month; however, SC-LA provided a longer duration of action than expected based on the dosing interval. This profile suggests that SC-LA will provide effective suppression of T over a longer period of time, permitting greater injection scheduling flexibility.